2015
DOI: 10.3892/mmr.2015.4683
|View full text |Cite
|
Sign up to set email alerts
|

Chelidonine induces mitotic slippage and apoptotic-like death in SGC-7901 human gastric carcinoma cells

Abstract: The aim of the present study was to investigate the effect of chelidonine on mitotic slippage and apoptotic-like death in SGC-7901 human gastric cancer cells. The MTT assay was performed to detect the antiproliferative effect of chelidonine. Following treatment with chelidonine (10 µmol/l), the ultrastructure changes in SGC-7901, MCF-7 and HepG2 cells were observed by transmission electron microscopy. The effects of chelidonine on G2/M phase arrest and apoptosis of SGC-7901 cells were determined by flow cytome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…It is plausible to assume that the transient effect exerted by chelidonine on the level of pSer-STAT3 in our experiments reflects the same cyclicality, i.e., chelidonine interferes with the machinery leading to activation of Cdk1. This hypothesis is supported by previous data demonstrating that the initial upregulation of cyclin B level, the activator for Cdk1, was followed by a decline upon chelidonine treatment in a gastric cancer cell line [21]. Furthermore, the level of pSer-STAT3 changed in a similar fashion in nocodazole-treated HeLa cells, where Cdk1 was active, whereas the total level of STAT3 did not change [14].…”
Section: Discussionsupporting
confidence: 85%
“…It is plausible to assume that the transient effect exerted by chelidonine on the level of pSer-STAT3 in our experiments reflects the same cyclicality, i.e., chelidonine interferes with the machinery leading to activation of Cdk1. This hypothesis is supported by previous data demonstrating that the initial upregulation of cyclin B level, the activator for Cdk1, was followed by a decline upon chelidonine treatment in a gastric cancer cell line [21]. Furthermore, the level of pSer-STAT3 changed in a similar fashion in nocodazole-treated HeLa cells, where Cdk1 was active, whereas the total level of STAT3 did not change [14].…”
Section: Discussionsupporting
confidence: 85%
“…(1) inducing caspase-dependent or caspase-independent cell death; (2) modulating the telomere length; (3) suppressing the NF-κB pathways; (4) inducing mitotic slippage and apoptotic-like death of human cancer cells. [73][74][75][76][77] In this study, we observed the potential application of chelidonine to the treatment of advanced HCC. We established two invivo HCC growth models to examine the in-vivo activity of chelidonine, namely the subcutaneous tumor model and intrahepatic tumor model.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the biological diversity of the secondary metabolites obtained from natural products provides us with new druggable agents, as well as novel options for chemical synthesis and structural modification 6772. Chelidonine could function as an antitumor agent via multi-mechanisms: (1) inducing caspase-dependent or caspase-independent cell death; (2) modulating the telomere length; (3) suppressing the NF-κB pathways; (4) inducing mitotic slippage and apoptotic-like death of human cancer cells 7377. In this study, we observed the potential application of chelidonine to the treatment of advanced HCC.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] To be specific, chelidonine treatment induced apoptosis in T98G glioma cells, MCF-7 and SK-BR-3 breast adenocarcinoma, HepG2 hepatoma, HeLa cervical cancer, SW620 colon cancer, head and neck squamous cell carcinoma HNSCC, human gastric carcinoma SGC-7901, and leukemia MT-4 cells, through caspase, cell cycle checkpoints and MAP Kinase pathways. 3,[6][7][8][9][10][11][12] In colon cancer Caco-2 and leukemia cell line CEM/ADR 5000, metabolic enzyme regulation by chelidonine reversed doxorubicin resistance. 13 Chelidonine was also reported to trigger autophagy, cellular senescence and blocking telomerase activity.…”
Section: Introductionmentioning
confidence: 99%